Surgically Assisted Rapid Palatal Expansion to Correct Maxillary Transverse Deficiency - Rachmiel, Adi (Ann Maxillofac Surg, 2020)
BACKGROUND: Transverse maxillomandibular discrepancies are widespread. Treatment is comprised of orthodontic expansion in patients younger than 15 years or by surgically assisted rapid palatal expansion (SARPE) in skeletally mature patients where the possibility of successful orthodontic maxillary expansion decreases as sutures close and resistance to mechanical forces increases. AIM: To present our experience of treating transverse maxillary deficiency using a unique L-shaped osteotomy and to demonstrate stable results. PATIENTS AND METHODS: 32 patients aged between 19 and 54 years exhibiting transverse maxillary deficiency. L-shaped osteotomy was performed laterally from the pterygoid plate posteriorly to above the roots of the second incisive anteriorly continuing with a vertical osteotomy between the lateral incisive and canine teeth toward the horizontal osteotomy. In 18 patients with dysgnathia, bimaxillary surgery was performed one year following the SARPE procedure. RESULTS: Mean transverse maxillary expansion of 6.2mm at the canine incisal and 6.4mm at the first molar occlusal regions were obtained. One year postoperatively results were relatively stable, 5.8mm and 6.2mm respectively. The SARPE procedure resulted in overcoming the maxillary buttress resistance, expansion of the anterior dental arch and bilateral distraction creating bone on both sides of the premaxilla contributing to better alignment of the anterior teeth and superior stability. CONCLUSIONS: We conclude that SARPE is an effective and stable method for addressing severe maxillary transverse discrepancy in adults while the unique osteotomy performed allowed for maintaining proper position of the premaxilla and maxillary midline and allowing for division of the newly created bone bilaterally thus resulting in a more stable outcome.